STUDY ON VIBRATION PROPERTIES OF COMPOSITE MATERIALS - (:unkn) unknown (INST MATERIALS PHYSICS, 2017)
The polymeric materials are used in a wide variety of fields for their several surpassing properties. The mechanical properties of polymers are, however, strongly influenced by various environmental factors. One of the principles for estimating the long-term behaviour of polymers may be a time-temperature superposition (equivalence), based on the viscoelastic properties of polymers varying with time and temperature. This is accepted that viscoelastic properties of flax in the epoxy materials related to some modes in the time/temperature domain. This relations are presented some formulas as WLF, Arrhenius and etc. In this work these theoretical attempt to understand the nature vibration behaviour depend to frequency-temperature relationship.
Keywords: vibration; composite; elasticity modulus